2017
DOI: 10.1248/bpb.b17-00127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Catechin Metabolites Produced by Intestinal Microbiota on Proliferation of HeLa Cells

Abstract: Eleven kinds of catechin metabolites produced from ( )-epigallocatechin (EGC) and ( )-epigallocatechin gallate (EGCg) by intestinal microbiota were evaluated for inhibitory activity on the proliferation of HeLa cells, which are human cervical cancer cells. Among the catechin metabolites, 1-(3,4,5-trihydroxyphenyl)-3-(2,4,6-trihydroxyphenyl)propan-2-ol (EGC-M2), 4-hydroxy-5-(3,4,5-trihydroxyphenyl)valeric acid (EGC-M7), and 5-(3,4,5-trihydroxyphenyl)valeric acid (EGC-M9) were found to show inhibitory activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Catechin hydrate was reaveled to demonstrate inhibitory activity on SiHa cell proliferation by mediating apoptosis compared with cells without treatment (44). A recent study indicated that catechinmetabolites EGCM7, and EGC-M9, produced from EGCG, inhibit the proliferation of the HeLa (HPV16/18+) cell lines; however, the inhibitory mechanisms of catechin metabolites, produced by intestinal microbiota against cervical cancer cells, have not been clarified (45). However, the mechanism underlying cell cycle arrest and apoptosis induction mediated by EGCG remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Catechin hydrate was reaveled to demonstrate inhibitory activity on SiHa cell proliferation by mediating apoptosis compared with cells without treatment (44). A recent study indicated that catechinmetabolites EGCM7, and EGC-M9, produced from EGCG, inhibit the proliferation of the HeLa (HPV16/18+) cell lines; however, the inhibitory mechanisms of catechin metabolites, produced by intestinal microbiota against cervical cancer cells, have not been clarified (45). However, the mechanism underlying cell cycle arrest and apoptosis induction mediated by EGCG remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The following catechin metabolites were prepared using the methods we reported previously. 13,14,25) Abbreviation of EGCG metabolites were defined as follows: Cell Culture Rat L6 myoblast cells were purchased from Sumitomo Dainippon Pharma Co., Ltd. (Osaka, Japan). L6 myoblast cells were cultured in Eagle's minimum essential medium (MEM; Nissui Pharma Co., Ltd., Japan) containing 10% heat-inactivated fetal bovine serum (FBS; Sigma-Aldrich Japan Co.…”
Section: Methodsmentioning
confidence: 99%
“…23) Furthermore, EGCG improved glucose uptake by increasing GLUT4 translocation in dexamethasone-induced insulin resistant L6 muscle cells through the activation of both AMP-activated protein kinase (AMPK) and phosphatidylinositol 3 kinase (PI3K)/Akt pathways. 24) However, we know of no report concerning glucose uptake ability of EGCG microbial metabolites into skeletal muscle and their antidiabetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The production of nitric oxide was inhibited by 5‐(3′,4′,5′‐trihydroxyphenyl)‐γ‐valerolactone . Catechin metabolites, such as 1‐(3,4,5‐trihydroxyphenyl)‐3‐(2,4,6‐trihydroxyphenyl) propan‐2‐ol, 4‐hydroxy‐5‐(3,4,5‐trihydroxyphenyl) valeric acid, and 5‐(3,4,5‐trihydroxyphenyl) valeric acid showed inhibitory activity on HeLa cell proliferation, unlike the control . In addition to these studies, how differences in intestinal microbiota affect metabolism needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…propan-2-ol, 4-hydroxy-5-(3,4,5-trihydroxyphenyl) valeric acid, and 5-(3,4,5-trihydroxyphenyl) valeric acid showed inhibitory activity on HeLa cell proliferation, unlike the control. [20] In addition to these studies, how differences in intestinal microbiota affect metabolism needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%